The Influence of Motivation, Business Capital, Entrepreneurial Knowledge, and Business Networks on Business Success - Putri Vavensy; Sarwo Edy Handoyo (International Journal of Management Science and Application, 2022)
Starting a business is not easy. Entrepreneurs face various kinds of difficulties in running their businesses. If difficulties cannot be overcome, it can worsen business performance and can even lead to bankruptcy. Entrepreneurs must be able to build a competitive advantage in their businesses. This can affect the sustainability of its business. Several factors influence business success. This study aims to analyze the effect of motivation, venture capital, entrepreneurial knowledge, and business networks on business success in the food and beverage business in Jakarta, Indonesia. The population of this study is all food and beverage business owners in Jakarta. The sample of this research is 100 food and beverage business owners in Jakarta. The technique of determining the sample using purposive sampling. Data collection was carried out using a google form questionnaire which was distributed online. Data were analyzed using the SmartPLS 3.0 application. The results of the study found that motivation, business capital, entrepreneurial knowledge, and business networks have a positive effect on business success. The results of this study are expected to contribute to the development of entrepreneurship and can provide input for entrepreneurs to achieve business success.